2016
DOI: 10.1007/s40520-016-0617-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-related hyperkyphosis: update of its potential causes and clinical impacts—narrative review

Abstract: The present study aims to qualitatively review the contributing factors and health implications of age-related hyperkyphosis. We conducted a narrative review of observational and cohort studies describing the risk factors and epidemiology of hyperkyphosis from 1955 to 2016 using the following key words: kyphosis, hyperkyphosis, posture, age-related hyperkyphosis, kyphotic posture, aetiology and causes. This review included 77 studies. Approximately 60–70 % of the most severe hyperkyphosis cases have no evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 71 publications
1
110
1
2
Order By: Relevance
“…Usually, thoracic kyphosis undergoes changes with aging, as it is often related to aspects such as, osteoporosis, obesity, sedentary lifestyle and muscular weakness (22,23,24,25), which are commonly observed in elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, thoracic kyphosis undergoes changes with aging, as it is often related to aspects such as, osteoporosis, obesity, sedentary lifestyle and muscular weakness (22,23,24,25), which are commonly observed in elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Classically a 'Dowager's Hump' (for which the term kyphosis originates from the Greek kyphos, a hump) is observed in the older female population who are at relatively high risk of osteoporosis. Women reportedly develop kyphosis earlier in life and to a greater degree than men (20) . Conceivably, older females with spinal kyphosis may have a higher proportion of underlying vertebral fractures versus degenerative changes as compared with males, which would lead to distinct sexspecific heritability estimates and genetic correlations with other endophenotypes.…”
Section: Thoracic Spinal Curvature: Heritability and Genetic Correlatmentioning
confidence: 94%
“…Women reportedly develop kyphosis earlier in life and to a greater degree than men. (20) Conceivably, older females with spinal kyphosis may have a higher proportion of underlying vertebral fractures versus degenerative changes compared with males, which would lead to distinct sex-specific heritability estimates and genetic correlations with other endophenotypes. Consistent with this suggestion, monozygotic twin studies have identified sex-specific differences in heritability of BMD.…”
Section: Thoracic Spinal Curvature: Heritability and Genetic Correlatmentioning
confidence: 99%
“…Thus, these changes in the muscle cause LBP even for a short period (e.g., while standing and walking) [29][30][31][32][33][34][35][36] . The relationship between spinal kyphosis and the structural and functional parameters of trunk muscles should be investigated 36) . A previous basic study suggested that the involvement of inflammation of the fascia in the back could alter the gait pattern in rodents 37) .…”
Section: ) Osteoporotic Pain Derived From An Osteoporotic Pathologymentioning
confidence: 99%